Avoidance, tolerance, and resistance to ectoparasites in nestling and adult tree swallows. (27th February 2018) - DeSimone, Joely G.; Clotfelter, Ethan D.; Black, Elizabeth C.; Knutie, Sarah A.
Abstract : We examined avoidance, tolerance, and resistance strategies of nestling and adult tree swallows Tachycineta bicolor in response to ectoparasitic blowflies Protocalliphora sialia . Tree swallows avoided settling in north‐facing nest boxes early in the breeding season. These boxes were more likely to be parasitized later in the season, suggesting that box selection may facilitate blowfly avoidance. After experimentally manipulating blowfly intensity, we found that nestlings were generally tolerant of parasitism. Parasites significantly reduced nestling blood hemoglobin but had no effect on nestling body mass, primary feather growth, age at fledging, or fledging success. Parents of parasitized nestlings did not increase their food provisioning rate to promote nestling tolerance. Adult female tree swallows demonstrated both tolerance and resistance: blowfly parasitism had no effect on adult hemoglobin and body mass, and those with higher P. sialia‐ binding antibody levels had fewer blowfly larvae in their nests. Nestling antibodies were unrelated to blowfly intensity. Despite considerable variation among years, our results suggest that the costs of blowfly parasitism to nestling and adult tree swallows are modest, and limited to blood loss in nestlings. Future work should examine the effects of reduced blood hemoglobin on fledgling survival and the importance of parasite‐specific antibodies.